1980
DOI: 10.1172/jci109758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neonatal modulation of cholesterol homeostasis on subsequent response to cholesterol challenge in adult guinea pig.

Abstract: A B S T R A C T Experiments were designed to study whether or not the mechanism of handling dietary cholesterol in adulthood can be modulated by the manipulation of cholesterol homeostasis during neonatal period. (b) no alteration in the fecal excretion of steroids, or (c) no alteration in the cholesterol 7a-hydroxylase activity when they were challenged with a high cholesterol diet. Early weaning did not influence the fecal excretion of steroids or cholesterol 7a-hydroxylase activity but resulted in a sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The most convincing evidence of longstanding effects of nutrition in infancy on blood cholesterol concentration comes from animal studies performed in rats, rabbits, guineapigs or baboons (Coates et al, 1983;Hahn & Koldovski, 1976;Hulbron et al, 1982;Li et al, 1980;McGill et al, 1996;Reiser & Sildlerman, 1972;Whatley et al, 1981). The most comprehensive animal data come from different experiments in baboons (McGill et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The most convincing evidence of longstanding effects of nutrition in infancy on blood cholesterol concentration comes from animal studies performed in rats, rabbits, guineapigs or baboons (Coates et al, 1983;Hahn & Koldovski, 1976;Hulbron et al, 1982;Li et al, 1980;McGill et al, 1996;Reiser & Sildlerman, 1972;Whatley et al, 1981). The most comprehensive animal data come from different experiments in baboons (McGill et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A new systematic review of the literature showed that breastfeeding is associated with increased mean TC and low density lipoprotein (LDL) levels in infancy but lower levels in adult life (Owen et al, 2002). This could partly be explained by the effect of early ingestion of a diet rich in cholesterol, leading to high plasma cholesterol, which in animal studies has been suggested to protect against high cholesterol challenges later in life (Reiser and Sidelman, 1972;Reiser et al, 1979;Li et al, 1980). However, the meaning of cholesterol concentration in early childhood for health in later life is still not clear, and we do not at present know what is the most favourable concentration of plasma lipids during infancy (Karlsland et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…31,32 This suggests that long-term cholesterol homeostasis could be affected by the level of dietary cholesterol in the infant diet. However, these effects were not seen in guinea pigs 10 and, among human fetuses, increases in hepatic LDL receptor activity were associated positively with gestational age and were correlated inversely with serum total cholesterol and LDL cholesterol levels. 40 The current study confirms feedback inhibition of cholesterol synthesis among human infants, dependent on exposure to dietary cholesterol.…”
Section: Discussionmentioning
confidence: 80%
“…Early exposure to dietary cholesterol appeared to "protect" against diet-induced hypercholesterolemia in adulthood, because adult male offspring exhibited an inverse relationship between serum cholesterol concentrations and the cholesterol content of their mothers' milk. Results from studies in a variety of species produced conflicting results; other rat studies supported 5 or refuted 6 the hypothesis, studies in pigs supported the hypothesis, 7 and studies in baboons 8,9 and guinea pigs 10 did not support the hypothesis.…”
mentioning
confidence: 97%